The Effect of Different Curing Temperatures on the Properties of Geopolymer Reinforced with Micro Steel Fibers - Amouri, M. S.; Fawzi, N. M. (Engineering, Technology & Applied Science Research, 2022)
In this study, geopolymer mortar was designed in various experimental combinations employing 1% micro steel fibers and was subjected to different temperatures, according to the prior works of other researchers. The geopolymer mortar was developed using a variety of sustainable material proportions (fly ash and slag) to examine the influence of fibers on its strength. The fly ash weight percentage was 50%, 60%, and 70% by slag weight to study its effect on the geopolymer mortar's properties. The optimal ratio produced the most significant results when mixed at a 50:50 ratio of fly ash and slag with 1% micro steel fibers at curing temperature 240oC for 4 hours through two days. The compressive strength of the geopolymer mortar increased by 11%, 11.5%, and 14% after 3, 7, and 28 days when utilizing fibers. The result shows that fly ash with a ratio of 50% by weight of slag improved the compressive strength of the mixture. It was discovered that a combination with 50% of the weight of fly ash with micro steel fibers, when treated at 240oC for curing age of 3, 7, and 28 days, had a flexural resistance rate of 28%, 30%, 33% higher than a mixture without fibers.